PRARANCANGAN PABRIK PHTHALIC ANHYDRIDE DARI NAPHTHALENE DAN UDARA KAPASITAS 80.000 TON/TAHUN - , NOVI WULANSARI; , Prof. Ir. Suryo Purwono, MA.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Phthalic anhydride plant is designed with capacity 80.000 ton/year. It is operated for 330 day/year. The purity of phthalic anhydride in product is 99,93% with maleic anhydride and naphthoquinone as impurities. The method for production of phthalic anhydride is partial oxidation of naphthalene using air. The raw materials are 99.421,66 ton/year naphthalene 99,9% and 1.118.915,90 ton/year air to produce 80.000 ton/year phthalic anhydride. Naphthalene solid is melted from the storage prior to further be evaporated. The pressure and temperature of naphthalene vapor and air are increased to the operating conditions of the fluidized bed reactor (3 atm and 360 oC). Products out from reactor are cooled and then are separated from non-condensable gas. Furthermore, phthalic anhydride is separated from maleic anhydride in the distillation column-01. Phthalic anhydride is purified from naphthoquinone in the distillation column-02. Phthalic anhydride 99,93% go to prilling tower. Product from prilling tower is phthalic anhydride prill (diameter = 3 mm). Phthalic anhydride is packed and is stored in storage. The plant of phthalic anhydride will be bulid in Cilegon, Banten. The area of plant is 100.000 m2 and it has 321 labour. The plant of phthalic anhydride with capacity 80.000 ton/year needs water 1.337.703,861 kg/hour, pressure air 400 m3/hour, 12.995,4965 electricity kW and fuel 1.140,6003 kg/hour. Fixed capital of phthalic anhydride plant is US$ 45,456,757.47 + Rp 244.554.676.901,73, working capital US$ 17,297,530.58 + Rp 36.631.450.571,92. Profit before taxes is Rp 192.712.735.480,10and profit after taxes is Rp 96.356.367.740,05. The economic evaluation shows that the plant has Return on Investment (ROI) before taxes 27,70%, after taxes 13,85%. Pay Out Time (POT) before taxes is 2,65 years, after taxes is 4,19 years. Break Event Point (BEP) 41,69%, Shut Down Point (SDP) 16,51% and Discounted Cash Flow Rate of Return (DCFRR) 19,34%. Based on the economic analysis, the design of phthalic anhydride plant from naphthalene and air with capacity ton/year is interesting to be studied further.